Financing practices in the German venture capital industry: An empirical assessment - Andreas Bascha; Uwe Walz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2002)
This paper investigates the financial contracting behavior of German venture capitalists against the results of recent theoretical work on the design of venture capital contracts, especially with regard to the use of convertible securities. First, we identify a special feature of the German market, namely that public-private partnership agencies require significantly lower returns than private and young venture capitalists. The latter are most likely to follow their North-American counterpart by refinancing themselves with closed-end funds. Second, with regard to financing practices it is shown that the use of convertibles, relative to other instruments, is influenced by the anticipated severity of agency problems.
urn:nbn:de:hebis:30-9982
Keywords: C24; G24; G32; 330; Venture Capital; Convertible Securities; Agency Theory